Evaluation on design-build procurement process in construction industry in Malaysia - Ikmal Izzat, Abdullah Karim (2019)
Design and Build (DB) delivery method is a united procurement approach where the selected builder will take sole responsibility for all aspects and activities of the project. This method also defined as a system where the clients directly pledge with the contractor to construct the project and play a decisive role to design and construct the project. However, DB can be organized by two ways which are; clients hire a competent design and build contractor in a same company or clients will hire an external consultant to assists the contractor during design and planning phase to ensure the smoothness performance of the project. For this study, the project sample selected is a construction projects in Malaysia that implementing DB method. The purpose of this study is to identify existing problems or issues in DB construction project in Malaysia, propose resolution to handle and manage major issues presence and also suggesting solutions to better improve overall performance of Design - Build project. In order to identify all the problems and evaluate proper solutions to mitigate problems, this study implementing quantitative method. For quantitative method, questionnaire forms are handed out during data collection session to the respondents. To analyze and generate the collected data, Content Analysis and Average Index Analysis are being utilized. From the assembled results, it can be conclude that, most of the respondents agreed that their project deal with inexperience workforce problem. This problem occur may due to the inefficient or improper work planning. Insufficient or improper work planning can be improved by establishing a well - planned master program that are practical and implemented on site. Finally, this study propose a Standard Operating Procedure (SOP) that will act as a guideline to construction teams in order to better improve the overall performance of DB project and reduce major problems.